The Unlikely Hero. The treatment of Maradona’s Death in American Media. - Lopez Medel, Ismael (Funes. Journal of narratives and social sciences, 2022)
The news coverage of a figure as complex as Maradona reflected his importance as an idolized sports figure, immensely popular despite his tumultuous existence. But media coverage also reflects a sociological view of sports heroes, and especially flawed ones. In this chapter, I look at the coverage of Maradona’s death in the United States, analyzing thirty-four media outlets across platforms. The study shows an informative character when reporting about Maradona, but also a detachment about his figure and legacy. The paper argues that the media analysis reflects the secondary social role of soccer in the United States in comparison with the rest of the world, acknowledging the importance of Maradona, but also viewing him as a foreign idol, and a failed one. We finally argue that Maradona’s history is unparalleled in the American sports landscape, and it is only understood when explored in depth.